The Power of Public Investment Management : Transforming Resources into Assets for Growth - Rajaram, Anand; Minh Le, Tuan; Kaiser, Kai; Kim, Jay-Hyung; Frank, Jonas (World Bank Group, Washington, DC, 2014)
This publication consists of seven chapters: building a system for public investment management; a unified framework for public investment management; country experiences of public investment management; approaches to better project appraisal; public investment management under uncertainty; procurement and public investment management; and public investment management for public-private partnerships.